TEACHER STRATEGY IN INTRODUCING SEX EDUCATION CHILDHOOD AT INSAN MULIA IT KINDERGARTEN, SEMARANG CITY - Ranika Herliyana; Sofa Muthohar; Muslam (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Sexual education has become an important issue amidst growing awareness of protecting children from violence and sexual harassment. Sexual education needs to be introduced to children from an early age so they can recognize risky sexual behavior and how to avoid it. Introducing sexual education is an important step in developing children’s basic understanding of body parts, privacy, and self-protection. The purpose of this study was to analyze the strategies used by teachers at Insan Mulia IT Kindergarten regarding introducing sexual education to early childhood. This study used a descriptive qualitative approach and analysis collected through observation, interview with Insan Mulia IT Kindergarten teachers, and documentation. The result showed that the teachers’ strategies provide a basic understanding of sexuality at Insan Mulia IT Kindergarten, including the use of teacher strategies such as movement and song, stories, and collaboration. The result showed that children were able to understand the introduction to sexual education provide by the teachers. This strategy was effective in increasing early childhood understanding of their bodies, the boundaries of touch, self-protection, and raising awareness of the importance of maintaining the privacy of their bodies. This study concludes that the introduction of sexual education to early childhood needs to be delivered with an approach that is appropriate to the development aspects and values that are supported in order create a positive learning environment.